Deprescribing of psychotropic medication in a 30-year-old man with learning disability. Issue 1 (20th December 2016) - Adams, Danielle; Sawhney, Indermeet
Abstract : A 30-year-old man with learning disability, living in a residential home with no documented mental health diagnosis, on the autistic spectrum was prescribed carbamazepine, olanzapine and propranolol to manage behaviour on a long-term basis. He was able to successfully discontinue both of his psychotropic medicines. The reduction was carried out in the community under the supervision of the learning disability psychiatrist. He is less tired, more alert and better able to express himself. He has expanded his activities and increased his access to the community. He is able to cope better with changes to his routine. His behaviours are well managed by the behavioural strategies in place and he has now been discharged by the psychiatrist to the general practitioner.